PELATIHAN PENULISAN ARTIKEL HASIL PENELITIAN TINDAKAN KELAS BERDASARKAN SRATEGY 4CS DALAM PENINGKATAN KOMPETENSI PROFESIONAL GURU - Aan Komariah; Dedy Achmad Kurniady; Yayah Rahyasih; Nugraha Suharto; Sururi Sururi; Zaini Hafidh (Universitas Pendidikan Indonesia, 2022)
This community service generally aims to improve the ability of teachers to write articles on the results of classroom action research which is expected to have a positive impact on position certification and promotion of teacher ranks/classes as well as increasing teacher professional competence. where the service implementers provide training and direct assistance to the trainees with a certain closeness and emotional bond, of course, by following the health protocols, including: wearing masks and/or face shields, washing hands before entering the room, checking temperature, maintaining a good distance between participants and others. participants and participants with resource persons. As for the results and discussion, this community service with the theme of Article Writing Training on Classroom Action Research Based on the 4cs Strategy in Increasing Teacher Professional Competence was carried out at SMPN 2 Padaherang, Padaherang sub-district, Padalarang Regency with a total of 115 participants. In addition, the work on the articles of the training participants in Writing Articles of Classroom Action Research Based on the 4cs Strategy in Improving Teacher Professional Competence will be published in the PAKAR GURU journal, a national-level journal that has a credit score of 2. So that this can help participants to be submitted in promotion.